Penggunaan Media Flashcard dalam Meningkatkan Kemampuan Kognitif Anak Usia 5-6 Tahun Di Kelompok Bermain Kenanga - Yusuf Hidayat; Risa Rahmawati; Imas Masri'ah; Suwarni; Lela Rosidah (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Flashcard media is a learning medium designed to optimize early childhood learning experiences through multisensory stimulation. This study aims to determine the use of flashcard media to improve the cognitive abilities of early childhood-aged children (5-6 years) in Kober Kenanga and to assess the extent of the impact of using flashcard media on the development of cognitive abilities in early childhood-aged children (5-6 years) in Kober Kenanga. The method employed in this study is qualitative under a phenomenological approach. The method used in this study is a qualitative approach with a phenomenological approach. In this study, the researchers act as the teacher assisted by other two teachers to conduct the learning on 15 early childhoods aged 5-6 years who are selected as the population and sample in this study. The results show that the use of flashcard media occurs well, at which 11 early childhoods (73.3%) are able to remember, understand, and match the alphabet A-Z, with the criteria developing of according to expectations (BSH). Meanwhile, the rest of the 4 early childhoods (26.7%) are still experiencing obstacles, with the criteria not yet developing (BB). Furthermore, when the use of flashcard media is combined with the singing method and the drilling technique, the results show that the entire 15 early childhoods (100%) can remember, understand, and match the letters of the alphabet A with the available symbols and images, with the criteria of developing very well (BSB).